Xanthone Glycosides from Swertia bimaculata with α-Glucosidase Inhibitory Activity - Yue, Yao-Dong; Zhang, Yu-Tang; Liu, Zhao-Xia; Min, Qiu-Xia; Wan, Luo-Sheng; Wang, Yong-Long; Xiao, Zuo-Qi; Chen, Jia-Chun (Planta Medica, 2014)
Seven new xanthone glycosides (1–7) were isolated from the n-butanol extract of Swertia bimaculata, together with six known compounds (8–13). Their structures were elucidated on the basis of extensive spectroscopic analyses (1D- and 2D-NMR, HRESIMS, UV, and IR) and comparison with data reported in the literature. All the compounds were evaluated for their α-glucosidase inhibitory activities in vitro, and compounds 3, 4, and 7 exhibited significant activities to inhibit α-glucosidase. Meanwhile the effects of different substitutions on the α-glucosidase inhibitory activity of xanthone glycosides from S. bimaculata are also discussed.
Keywords: Swertia bimaculata; Gentianaceae; xanthone glycosides; α-glucosidase inhibition